2016
DOI: 10.1021/acs.joc.6b02024
|View full text |Cite
|
Sign up to set email alerts
|

Access to 6a-Alkyl Aporphines: Synthesis of (±)-N-Methylguattescidine

Abstract: (-)-N-Methylguattescidine (3) is an alkaloid recently isolated from Fissistigma latifolium and assigned as a rare example of a 6a-alkyl aporphine. Herein, we report the synthesis of (±)-3 and the des-hydroxyl derivative 4 using our previously reported ortho-phenol arylation methodology mediated by the XPhos precatalyst as a key synthetic step. In addition, substituents on the aryl halide portion of the ortho-phenol arylation substrates significantly influenced the formation of an oxidized side product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Subsequent oxidation of electron-rich arene 8 with DMP directly generated benzoquinone 9a in 46% yield, with no detection of desired 1-benzoyl-substituted analogues 9. 39 The synthetic route of 1-benzyltetrahydroisoquinolines 13b and 14b is depicted in Scheme 2. Condensation reaction of commercially available 2-bromophenylacetic acid 10 with various phenylethylamines 11a−f 40,41 gave amides 12a−f, respectively, followed by Bischler−Napieralski cyclization with PCl 5 /POCl 3 /P 2 O 5 and reduction with NaBH 4 , which furnished tetrahydroisoquinolines 13a−f, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Subsequent oxidation of electron-rich arene 8 with DMP directly generated benzoquinone 9a in 46% yield, with no detection of desired 1-benzoyl-substituted analogues 9. 39 The synthetic route of 1-benzyltetrahydroisoquinolines 13b and 14b is depicted in Scheme 2. Condensation reaction of commercially available 2-bromophenylacetic acid 10 with various phenylethylamines 11a−f 40,41 gave amides 12a−f, respectively, followed by Bischler−Napieralski cyclization with PCl 5 /POCl 3 /P 2 O 5 and reduction with NaBH 4 , which furnished tetrahydroisoquinolines 13a−f, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This discovery was successfully applied toward the stereoselective synthesis of (À )-lirinine (80) 80) [126] (Scheme 15a). From 2015 to 2019, Cuny et al demonstrated the great potential of the catalytic system disclosed in 2012 [126] through the synthesis of several aporphine compounds, including (À )-oliveroline (81), [127] (À )-nornuciferidine (82), [127] and (�)-N-methylguattescidine (83), [128] as well as 7hydroxyaporphines (e. g., 84) [129] and 8-aryloxyaporphines (e. g., 85) [130] with important pharmacological properties (Scheme 15b).…”
Section: Palladium-catalyzed Reactionsmentioning
confidence: 99%
“…The first approach is derived from a retrosynthetic analysis involving a hypothetical one-bond disconnection, affording primarily 1-benzyl-1,2,3,4-tetrahydroisoquinoline compounds. This strategy is based on biosynthetic routes and has been implemented using different transformations, including the Pschorr cyclization, photochemical reactions, and palladium-catalyzed cyclizations [122,[124][125][126][127][128][129][130][131][132][133][134][135][136][137][138] (Scheme 1). Intramolecular cyclizations using phenolic oxidative coupling reactions [62,139] and via generation of arynes tethered with aromatic nucleophiles [140] have not been addressed in this article.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclization and silyl deprotection of 114 gave an 80% yield of the isoquinoline nucleus 115 which was then subjected to ortho-phenol arylation with the XPhos precatalyst furnishing not only the desired arylated product 116a, but also the oxidized derivative 116b in a 53:47 ratio and a combined yield of 96% (Scheme 16). 100 However, both products were easily converted into the respective aporphine derivative 117 after O-demethylation and C=C reduction procedures. This intermediate 117 was converted into 119 upon treatment with CH 2 I 2 and reprotection of the hydroxy group in 48% yield over two steps.…”
Section: Review Syn Thesismentioning
confidence: 99%
“…The reduction of 119 with DIBAL-H gave 7-hydroxyaporphine (120), and oxidation and O-deprotection of 120 furnished N-methylguattescidine (122) as a racemic mixture in 12% overall yield (Scheme 16). 100 With the current interest in the development of alternative methodologies for the synthesis of β-carbolines, especially substituted at C3 and C4 positions, in 2010 Padwa and co-workers 101 reported the use of gold(III)-catalyzed cyclization reaction for the construction of the β-carboline core. Starting from the indole derivative 123, the reactivity of the resulting indole-substituted N-propargylamide 124 was explored during chemoselective C-C bond formation (Scheme 17).…”
Section: Review Syn Thesismentioning
confidence: 99%